DETERMINAN OBESITAS DAN IMPLIKASI KEBIJAKAN DALAM PENCEGAHAN DAN PENANGGULANGAN OBESITAS DI INDONESIA - Sulistyani Prabu Aji; Antonia Morita Iswari Saktiawati; Nur Ani; Susanti Anggraeni (Journal of Midwifery and Health Administration Research, 2022)
Bacground: The prevalence of overweight and obesity in the adult group in Indonesia has increased compared to the previous year. The determinants of obesity are complex, and can differ between regions. The right policy, in accordance with the determinants, plays an important role in efforts to reduce the prevalence of obesity. This study aims to identify the determinants of overweight and obesity in Indonesia and policies that support reducing the prevalence of overweight and obesity based on the significant determinants found. Methods: Data sources come from the Ministry of Health, the Central Statistics Agency, and the Ministry of Agriculture for 34 provinces in Indonesia. Literature on policy analysis is searched on Google, IPB University repositories, relevant ministry websites, PubMed, ScienceDirect, and MEDLINE. Multiple regression analysis is performed to identify determinants of overweight and obesity. Results: The proportion of overweight and obesity in Indonesia is 35.4%, with the proportion of the population with low physical activity of 33.5%. The Five-E approach was used to analyze policies related to the Healthy Community Movement Policy (HMC or known as GERMAS in Indonesia) and the inclusion of fat content on food labels is a policy for preventing and overcoming overweight, which was done related to the consumption of vegetables, fats, and oils. Result: The effectiveness of the policy is still not optimal even though the policy is efficient. Improvement of policy implementation needs to be done by optimizing the implementation of follow-up monitoring and evaluation of program policy implementation.